PARENTING PATTERNS OF PARENTS WORKING IN COMPANIES ON CHARACTER EDUCATION OF CHILDREN REVIEWING FROM ISLAMIC RELIGIOUS EDUCATION PERSPECTIVE - Eriansyah Kamal; Aqil; Acep Nurlaeli (al-Afkar, Journal For Islamic Studies, 2021)
In the process of character education of children, parents have a very important role in guiding and shaping the character of children, because children are a gift and mandate from Allah SWT, children are born to earth in a holy state, then it is their parents who influence their children's behavior So in any condition, no matter how busy parents are, they are obliged to guide and direct their children in a positive direction so that morality is created. This study aims 1) to determine the role of parents who work on children's character education, 2) the role of schools in shaping children's character so that Islamic character is realized, 3) obstacles and efforts made in educating children's character. Determination of research subjects was carried out by determination by researchers (purposive sampling), namely parents who worked in companies that sent their children to school at SDIT Harapan Ummah grades 4-6. The research approach is qualitative with descriptive research type. The data was collected by using interview techniques and data processing using qualitative analysis techniques. The results showed that: (1) Parenting patterns of parents who work in companies on the formation of children's character are different, firstly applying democratic parenting, secondly permissive parenting and thirdly authoritarian parenting. (2) The role of schools in shaping the character of students by training children with positive Islamic character habits, making programs that build children's character, and establishing coordination with parents in monitoring children's development. (3) the obstacles faced by parents in educating children's character due to lack of knowledge about parenting and role models from parents, lack of time with children and not being istiqomah in educating children's character. So parents should have concepts and provisions in educating children, because the role of parents is very important in the development and formation of children's character for the realization of Islamic character.